Reviewed work: Portuguese Studies on Medieval Illuminated Manuscripts - B Penafiel, A (Modern Humanities Research Association, 2019)
Book review of 'Portuguese Studies on Medieval Illuminated Manuscripts' by Maria Adelaide Miranda and Alicia Miguélez Cavero